2008
DOI: 10.1177/001440290807400406
|View full text |Cite
|
Sign up to set email alerts
|

Giving Voice to Parents of Young Children with Challenging Behavior

Abstract: In recent years, there has been increased interest in the science of child development, particularly relative to early childhood (i.e., birth to 5 years) and children with challenging behavior. A broad interest in brain-behavior relationships and prevention services for young children has led to a renewed interest in the developmental significance of early life experiences (National Research Council & Institute of Medicine, 2000). Armed with an increasingly large body of neuroscience research, researchers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 74 publications
1
50
0
Order By: Relevance
“…What does it mean to give voice? An informal examination of psychology research articles drawing from this concept suggests that "to give voice" means to "represent" previously "unheard" experiences and accounts (e.g., Harper, Jernewall, & Zeal, 2004;Worcester, Nesman, Raffaele Mendez, & Keller, 2008). Often, studies aiming to amplify previously unheard voices incorporate qualitative methods.…”
Section: Give Voice To Immigrants: Immigrant As a Research Collaboratormentioning
confidence: 99%
“…What does it mean to give voice? An informal examination of psychology research articles drawing from this concept suggests that "to give voice" means to "represent" previously "unheard" experiences and accounts (e.g., Harper, Jernewall, & Zeal, 2004;Worcester, Nesman, Raffaele Mendez, & Keller, 2008). Often, studies aiming to amplify previously unheard voices incorporate qualitative methods.…”
Section: Give Voice To Immigrants: Immigrant As a Research Collaboratormentioning
confidence: 99%
“…Several studies on comparable topics were suggestive of sample size. Worcester, Nesman, Mendez, and Keller (2008) interviewed seven families in a phenomenological study of parents raising children with behavioral issues. Seven participants were engaged in a phenomenological study of rape victims' recovery (Smith & Kelly, 2001).…”
Section: Data Collection Strategymentioning
confidence: 99%
“…Worcester, Nesman, Raffaele, Mendez, and Keeler [11] found that parents of young children M A N U S C R I P T…”
Section: The Role Of the Physicianmentioning
confidence: 99%